Ventral colporectopexy for overt rectal prolapse and obstructed defaecation syndrome: a systematic review. (February 2015) - Gouvas, N.; Georgiou, P. A.; Agalianos, C.; Tan, E.; Tekkis, P.; Dervenis, C.; Xynos, E.
Abstract Aim Laparoscopic ventral rectopexy (VR) with the use of prosthesis has been advocated for both overt rectal prolapse (ORP) and obstructed defaecation syndrome (ODS). The present study reviews the short‐term and functional results of laparoscopic VR. Method A search was performed of MEDLINE, EMBASE, Ovid and Cochrane databases on all studies reporting on VR for ORP, ODS and other anatomical abnormalities of the pelvic floor from 2004 until February 2013. No language restrictions were made. All studies on VR were reviewed systematically. The main outcomes were intra‐operative complications, conversion, procedure duration, short‐term mortality and morbidity, length of stay, recurrence of ORP, recurrence of anatomical disorder, faecal incontinence and constipation, quality of life (QoL) score and patient satisfaction. Quality assessment and data extraction were performed independently by three observers. Results Twenty‐three studies including 1460 patients were eligible for analysis. The conversion rate ranged from 0 to 14.3%. No mortality was reported. The immediate postoperative morbidity rate was 8.6%. Length of stay ranged from 1 to 7 days. A significant improvement in constipation and incontinence symptoms was observed in the postoperative period for both ORP and ODS (chi‐square test, P < 0.0001). Conclusion Laparoscopic VR is a safe and effective procedure for ORP and ODS. Longer follow‐up is required, and studies comparing VR with standard rectopexy and stapled transanal rectal resection are not yet available.